Papua New Guinea : 2022 Article IV and the Staff Monitored Program-Press Release; Staff Report; and Statement by the Executive Director for Papua New Guinea. (IMF Staff Country Reports; Country Report ;, 2022)
Papua New Guinea (PNG)'s economy is weathering the pandemic well, despite many challenges. Real GDP in 2022 is projected to exceed its 2019 level, and the medium-term outlook is positive, supported by investment in (and revenues from) the resource sector. The war in Ukraine is impacting PNG through higher commodity prices and higher inflation, with the former leading to a stronger balance of payments and higher fiscal revenues, since PNG is a large commodity producer. Risks remain skewed to the downside and include a worsening health situation given the low vaccination rate, volatility in commodity prices, and political instability.